The Alignment of ESP in Teaching Activities and Materials at Vocational High School - Aziz, Agda Faisal; Anjaniputra, Agung Ginanjar (Fakultas Sastra - Universitas Muslim Indonesia, 2025)
This study aims to analyze the alignment of English for Specific Purposes (ESP) in teaching activities and teaching materials at Vocational High Schools (SMK) in Indonesia, especially in the context of the Merdeka Curriculum. A descriptive qualitative approach was used to explore teachers’ strategies, challenges, and recommendations in implementing ESP. the research participants consisted of three English teachers from three vocational high schools in Magelang City with different expertise programs, namely hospitality, nursing, and engineering. Data were collected through in-depth interviews and analyzed using a systematic thematic analysis model. The results show that teachers apply several strategies to align ESP with students’ needs, such as collaborative needs analysis with vocational teachers and industry professionals, work context-based activity design (e/g/ VR simulation in hospitality, role-play in nursing, and engineering projects), and diversification of material sources by utilizing digital technology. However, the main challenges include the mismatch of the national curriculum which is still oriented towards General English (EGP), limited ESP support facilities, and the gap in teacher competence in mastering technical content in vocational fields. Teachers recommend the development of a structured ESP curriculum based on majors, increased collaboration with industry, and hybrid training to strengthen teacher capacity. This finding confirms the need for multi-stakeholder synergy to optimize ESP learning in vocational high schools to be relevant to the needs of the world of work.